Tabarruk sebagai Tradisi Sosial-Religius : Analisis Dircuscive Tradition Talal Asad di Kalangan Pesantren - Jad Maula; Nashrulloh (Al-Kindi, 2026)
This article explores how the practice of tabarruk is understood and carried out in Islamic boarding schools through the perspective of Talal Asad's discursive tradition. This approach opens up a broader space for understanding tabarruk through text and context. By combining open-ended questionnaires and brief interviews, this study traces how tabarruk is formed and passed down through religious discourse, behavioral etiquette, and the authoritative role of kiai in the daily life of Islamic boarding schools. The results show that elements such as sanad, ijazah, and the legitimacy of a kiai serve as the main determinants of the validity of tabarruk as well as the boundaries that distinguish it from practices that are considered excessive or deviant. This confirms that the pesantren tradition applies through a combination of texts and bodily practices manifested in manners, gestures, and close relationships between kiai and santri. This study concludes that tabarruk is not merely a ritual of seeking blessings, but a process of forming religious identity and subjectivity that takes place through interactions between religious discourse, kiai authority, and daily practices among pesantren communities. The results of this study provide an important contribution to understanding how religious traditions survive, adapt, and gain legitimacy amid social changes in the development of modern pesantren.